B12Fn0/− (n = 1–6) series: when do boron double chain nanoribbons become global minima?. Issue 47 (22nd November 2017) - Bai, Hui; Bai, Bing; Zhang, Lin; Huang, Wei; Zhai, Hua-Jin; Li, Si-Dian
Abstract : Boron double chain B12 F n 0/− species provide new examples for ribbon aromaticity and powerful support for the F/H/Au/BO analogy. Abstract : We present an extensive density-functional and wave function theory study of partially fluorinated B12 F n 0/− ( n = 1–6) series, which show that the global minima of B12 F n 0/− ( n = 2–6) are characterized to encompass a central boron double chain (BDC) nanoribbon and form stable BF2 groups at the corresponding BDC corner when n ≥ 3, but the B12 F 0/− system maintains the structural feature of the well-known quasi-planar C 3v B12 . When we put the spotlight on B12 F6 0/− species, our single-point CCSD(T) results unveil that albeit with the 3D icosahedral isomers not being their global minima, C 2 B12 F6 (6.1, 1 A) and C 1 B12 F6 − (12.1, 2 A) as typical low-lying isomers are 0.60 and 1.95 eV more stable than their 2D planar counterparts D 3h B12 F6 (6.7, 1 A′) and C 2v B12 F6 − (12.7, 2 A2 ), respectively, alike to B12 H6 0/− species in our previous work. Detailed bonding analyses suggest that B12 F n 0/− ( n = 2–5) possess ribbon aromaticity with σ plus π double conjugation along the BDC nanoribbon on account of their total number of σ and π delocalized electrons conforming the common electron configuration (π 2( n +1) σ 2 n ). Furthermore, the simulated PES spectra of the global minima of B12 F n − ( n = 1–6) monoanions may facilitate their experimental characterization in the foreseeable future. Our work provides new examples for ribbon aromaticity and powerful support for the F/H/Au/BO analogy.